Study the Effect of Scattering and Disperse Radiation on Equivalent Dose Rate for Al & Pb Shields - Baghdad Science Journal (مجلة بغداد للعلوم)
The effects of scattering and secondary radiation generated inside the material on dose equivalent rate where studied using Co60 and Cs137 sources of activity (199.8 , 177.6) MBq , respectively for different thicknesses of Al , Pb and Pb- glass . The results showed that the equivalent rate increases when the effect of scattering was included for Al and Pb shields with cobalt-60 source of energy 1.25 MeV ; and decreases for Pb shield with Cs-137 source of energy 0.662MeV .The results showed also that the atomic number of The material effects the dose equivalent rate . The Pb-glass shield was found to be more efficient in absorption than other shields.